The miR169b/NFYA1 module from the halophyte Halostachys caspica endows salt and drought tolerance in Arabidopsis through multi-pathways - Ji, Jieyun; Zeng, Youling; Zhang, Suwei; Chen, Fangyuan; Hou, Xianfei; Li, Qiang (Frontiers in Plant Science, 2023)
Salt and drought are the major abiotic stress factors plaguing plant growth, development and crop yields. Certain abiotic-stress tolerant plants have developed special mechanisms for adapting to adverse environments in the long process of evolution. Elucidating the molecular mechanisms by which they can exert resistance to abiotic stresses is beneficial for breeding new cultivars to guide agricultural production during harsh environments. Halostachys caspica, a perennial halophyte belonging to Halostachys in Amaranthaceae, is an extremely tolerant to drought and salinity stresses, which are commonly grown in the saline-alkali arid desert area of Xinjiang, China. However, the molecular mechanism of stress tolerance is unclear. In this study, we first validated that HcNFYA1 was targeted by HcmiR169b and then elucidated the functions of HcmiR169b/HcNFYA1 module in plant tolerance to various abiotic stresses. HcmiR169b/HcNFYA1 module enhanced plant tolerance to environmental stresses at different physiological, biochemical and molecular levels. Our study confirmed that the HcmiR169b/HcNFYA1 module confers the salt and drought tolerance to plants by enhancing ABA synthesis and ABA signal transduction pathways, maintaining ROS homeostasis and the stability of cell membrane by the expression patterns of both miR169b and HcNFYA1 in H. caspica and the functions of Arabidopsis heterologously expressing HcmiR169b and HcNFYA1, individually, under salt and drought stress. HcNFYA1 is expected to be a candidate gene to improve plant resistance to various stresses.